2008
DOI: 10.1007/s10552-008-9232-8
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric characteristics and mammographic parenchymal patterns in post-menopausal women: a population-based study in Northern Greece

Abstract: Chest circumference as a measure of upper body fat adiposity appears to be a stronger determinant of mammographic patterns than body fat distribution (measured as WHR). A heavy body build in adulthood is associated with decreased mammographic density. Further studies are necessary to confirm our results, ideally prospective cohorts, looking at the effect of anthropometric determinants on mammographic pattern changes over time and breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…It was also found that in BMIs of 25-29, most of the cases (121 subjects) (28.3%) were in the high-density group and Fisher's exact test showed a significant association between BMI and dense view in mammography. These results also correspond with the study of Riza [12]. Overall, of the studied variables, age, BMI and breast cup size showed inverse relationships with density of breast tissue in mammography, while menstrual status can have a direct effect on the density of breast tissue in mammography.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was also found that in BMIs of 25-29, most of the cases (121 subjects) (28.3%) were in the high-density group and Fisher's exact test showed a significant association between BMI and dense view in mammography. These results also correspond with the study of Riza [12]. Overall, of the studied variables, age, BMI and breast cup size showed inverse relationships with density of breast tissue in mammography, while menstrual status can have a direct effect on the density of breast tissue in mammography.…”
Section: Discussionsupporting
confidence: 90%
“…Breast tissue density is the strongest factor in the increased risk of breast cancer and various studies have indicated that women with a high density of breast tissue are 4-6 times in higher risk of breast cancer than women with low breast tissue density [5,[7][8][9][10][11][12][13]. In total, in different studies, various factors such as age, hormones usage, factors associated with parents, body mass index (BMI) and reproductive factors have been considered effective on breast tissue density, but no definitive cause for this issue is known yet [8][9][10][11][12][13][14]. Given that the increased density of breast tissue can lead to increased risk of breast cancer, using intervention strategies for reducing its density will be very important.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of radiotherapy most easily noticed on photographs are changes in size and shape, with breast shrinkage the commonest effect. In large-or heavy-breasted women, the major component of the breast by volume is adipose tissue [30,31]. This raises the possibility that adipose tissue in large-or heavy-breasted women is, in some way, more sensitive to the effects of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism for the relationship between body size indices and breast cancer risk is still uncertain, and greater height and obesity may increase the risk of breast cancer through their effects on the components of breast tissue. However, the associations of body size indices and mammographic density have not been in accordance with the associations between the body size indices and breast cancer in studies of Western populations (19,20) as well as of Singaporean Chinese women (21,22). Replication of these findings in other Asian populations would provide strong evidence that body size increases the risk of breast cancer through another mechanism than their influence on breast tissue components.…”
Section: Introductionmentioning
confidence: 95%